Changing the organizational culture to transform the economy: The case of Greece - Boufounou, Paraskevi; Argyrou, Maria Despoina (Frontiers in Research Metrics and Analytics, 2022)
Organizational Culture determines companies’ ability to adapt, transform and innovate, directly affecting their profitability and competitiveness. However, the same applies for the public sector as well, since, now more than ever, it has to be agile in order to shield its society and economy against the modern challenges (such as COVID-19, climate change, digitalization, etc). This paper uses the case of Greece as an example to present the need for change in the organizational culture to unlock its development and growth potentials through transformation, adaptation, and innovation. To support our argument, we combine the findings of the international literature regarding the relationship between organizational culture and the above-mentioned elements, as well as empirical evidence from Greece. In particular, we assess the Organizational Culture pertaining in the major sector reforms that took place in Greece, as a result of the recent economic and financial crisis, by presenting and evaluating comparative empirical findings on the characteristics of the prevailing and desired future organizational culture. Examining and comparing the results of previous studies in Greece that used the OCAI questionnaire survey in both the private (banking and telecoms) and the public sector (social security, public revenues authority and hospitals), two interesting results arise: i) there is a clear distinction between the public sector and the private sector, with the former being characterized mainly by “Hierarchy Culture”, while the latter by “Market Culture”, and ii) in both sectors and in all industries/services the desired to prevail in the future organizational culture is the “Clan Culture”. These findings are of immense importance as organizational culture issues play a key role in formulating future strategic plans, enabling the development of key sectors of the Greek economy and enhancing effective governance and social services. Concisely, our results draw useful conclusions for policy implications and for academics, implying that there is an emergent need for organizational transformation in both the private and public sectors in Greece, which can be achieved through new innovative methods of organization and operation, creating a new more agile, adaptive and innovative culture.